The Effect of The Use of ChatGPT on Student’s Learning Motivation in PAI Subjects at SMK Permata Negeri Garut - Fuad Munawar; Ujang Dedih; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2026)
This research was motivated by the problems that occurred at SMK Permata Negeri Garut, where the results of an interview with one of the students at SMK Permata Negeri Garut revealed that they were more enthusiastic about participating in the learning process in vocational subjects than other subjects because it involved more technology in the learning process which made them more enthusiastic and enthusiastic in participating in the learning process. This study aims to find out how much influence the use of ChatGPT has on students' learning motivation in PAI subjects in class XI TKJ SMK Permata Negeri Garut. This research is based on the idea that students' learning motivation is influenced by the use of learning media, one of which is artificial intelligence-based learning media, namely ChatGPT. On this basis, the use of appropriate learning media can increase learning motivation, and vice versa. This study uses a quantitative approach and a descriptive method, with correlation analysis techniques. The population in this study is class students at SMK Permata Negeri Garut. The sample he used was class XI TKJ as many as 36 people. The data collection method uses observation, questionnaires, and interviews. In conclusion, this study shows that the use of ChatGPT significantly affects students' motivation to learn. Although the measurable level of relationship is low, the existence of statistical significance shows that ChatGPT has the potential to improve the quality of learning. These findings make an important contribution to the literature and understanding of the use of technology in educational contexts, as well as provide a prospective view for future research development and practical implementation.